Home Care Holistic on the Change of Anxiety and Depression for the Patient with Stroke Ischemic - Luluk Widarti; Krisnawati Krisnawati (Jurnal Ners, 2012)
Introduction: Stroke is the main cause of long-term disability. It was reported that one third out of stroke survivors showed dementia in three months after stroke. Stroke patients need medication and palliative caring so that home-care is highly recommended. In Indonesia, home-care nursing for ischemic stroke has not yet been optimally applied in caring patient with stroke. The objective of thestudy was to examine the effect of home care holistic nursing on the change of anxiety and depression for the patient with stroke ischemic.Method: An experimental research with quasy experimental speciﬁcally nonrandomized pre-post test control group design was applied in this study. The study was conducted in Surabaya by selecting ischemic stroke patients after being hospitalized at "A-Seruni was, Medic IRNA, Dr. Soetomo hospital". A sample of size 40 patients was divided equally into two groups, control and treatment groups. The treatment and control groups respectively received holistic home care and home care. The depression and anxiety level were measured by using questionnaires technique. The data were analyzed by using Levene's test for homogeneity of variance, and t-test.Result: The result showed that there were signiﬁcantly different between both groups for psychological response such as anxiety with p-value = 0.000, depression with p = 0.000.Discussion: It was concluded that holistic home care could improve the psychological responses by decreasing anxiety and depression level in ischemic stroke patients. It is recommended to make standard operational procedure of holistic home care that can be implemented by all health personnel who take care ischemic stroke patients.